The Impact of Motivation and Work Discipline on Employee Performance in the Environment of State-Owned Enterprises in Solok City - Nasrah, Rasidah; Sriyanti, Esi; Darmawan, Arifki (International Journal of Social Science and Community Service, 2025)
The study took place at PERUMDA Pincuran Gadang Drinking Water in Solok City with the aim of investigating the influence of work motivation and discipline on employee performance. The research involved 89 employees from the company, selected using the Total Sampling method. Data was collected through questionnaires and analysis revealed that both work motivation and discipline have an impact on employee performance. The multiple linear regression analysis yielded the formulation Y = 10.074 + 0.353X? + 0.409X? + e. The coefficient of determination elucidates that 52% of the fluctuation in Employee Performance (Y) can be ascribed to the influence of Work Motivation (X?) and Work Discipline (X?), whereas the residual 48% is attributable to extraneous variables beyond the purview of this inquiry. Findings from the t-test evince that both Work Motivation and Work Discipline, when considered in isolation, exert a statistically significant and favorable bearing on Employee Performance, as evidenced by t-statistic values surpassing their respective critical thresholds. Furthermore, the F-test substantiates that, in concert, Work Motivation and Work Discipline wield a consequential and substantive impact on Employee Performance, underscored by the F-statistic value (41.110) exceeding the F-table value (3.12) and a significance probability markedly inferior to the 0.05 criterion (0.000).